Cut & Splice: Reading Judges 19 Cinematically - Hurlbert, Brandon M. (Biblical interpretation, 2022)
What is the purpose of the violence in Judges 19 and what does this narrative aim to accomplish in its readers? Phyllis Trible (1984), Cheryl Exum (1993), and more recently, Margaret Atwood (2019), suggest that this violence is viewed positively by the narrator and serves to reinforce patriarchal ideology. I propose that a different conclusion may be reached by adopting a ‘grammatical-cinematic’ approach. The goal of this approach is to read the biblical narrative through film, i.e., to tell the biblical story in the language of the cinema by focusing on the ‘cinematic sensibilities’ of the text. Using examples from Quentin Tarantino’s Django Unchained, I argue that this approach can recover the agency and dignity of the woman and better visualize the brutality of violence. Finally, I argue that one can understand the object of the author’s critique to be the events and characters of the narrative.